The Use of History of Science as a Cultural Tool to Promote Students' Empathy with the Culture of Science - (:unkn) unknown (EDAM, 2012)
It is difficult for students to understand historical settings, connect to today's world, interpret and appreciate scientists' efforts within current perspectives. Empathizing with historical characters and events can mediate understanding nature of physics for students. The purpose of this study was to investigate the effect of history of science on students' empathy with the historical characters and the events. With regards of socio-cultural theory, empathy was defined as a cultural tool, which mediates between students and the science society. The study was conducted in a private high school with participation of twenty-one 9th grade students in physics class for the unit of The Nature of Physics. A qualitative case-study method was employed. Data resources were video and audio recordings, field notes, students' tasks, interviews, and surveys. After transcribing and categorizing, the data were analyzed and patterns were organized. The findings supported eight aspects of empathy: Making Personal Connections, Imagination, Identification, Humanization, Understanding the Events, Understanding Different Perspectives, Understanding the Tentativeness of the Conclusions and Taking Perspectives. The results supported that students could interact with the culture of science with the use of the aspects of historical empathy. The use of the aspects of empathy attracted students' interest in physics lesson. The results are also promising for students' understanding nature of science.
Keywords: History of Science; Empathy; Physics Education